2023
DOI: 10.1002/joa3.12865
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of detecting arrhythmia is higher with 7‐day continuous electrocardiographic patch monitoring than with 24‐h Holter monitoring

Abstract: Background: Detecting high-risk arrhythmia is important in diagnosing patients with palpitations. We compared the diagnostic accuracies of 7-day patch-type electrocardiographic (ECG) monitoring and 24-h Holter monitoring for detecting significant arrhythmias in patients with palpitations. Methods:This was a single-center prospective trial with 58 participants who presented with palpitations, chest pain or syncope. Outcomes were defined as the detection of any one of six arrhythmias, including supraventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the duration of ECG monitoring and the use of monitoring devices greatly improved the detection of arrhythmia recurrence after catheter ablation. 1 , 4 6 Generally, a 24-h Holter ECG examination is most often used to identify arrhythmia recurrence after catheter ablation. However, this procedure requires that patients visit the hospital several times to undergo the examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the duration of ECG monitoring and the use of monitoring devices greatly improved the detection of arrhythmia recurrence after catheter ablation. 1 , 4 6 Generally, a 24-h Holter ECG examination is most often used to identify arrhythmia recurrence after catheter ablation. However, this procedure requires that patients visit the hospital several times to undergo the examination.…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate of arrhythmia was significantly lower with the 24-h Holter ECG than with 7-day ECG monitoring in patients after catheter ablation. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6) Nonetheless, they offer considerable advantages over traditional methods such as Holter recording, particularly in diagnosing arrhythmias, owing to their long-term duration of monitoring. 7) 8) 9) 10) …”
Section: Introductionmentioning
confidence: 99%
“…Kim and colleagues demonstrated that a 7‐day patch‐type continuous electrocardiogram (ECG) monitor (MEMO patch®) had acceptable feasibility and efficacy in detecting arrhythmias when compared with conventional 24‐h Holter ECG monitoring. 1 Several concerns have been raised.…”
mentioning
confidence: 99%